European approaches to recognition of informal learning - potentials regarding ICT-components : paper - Annen, Silvia [Verfasser] (My University, 2012)
"In Europe the topic recognition of informal learning becomes more and more important (cf. e.g. Werquin/OECD 2007). At the same time the Europe-wide as well as the national approaches dealing with recognition are rather diverse. To present the results of a systematic analysis of selected European approaches is the aim of this paper. Furthermore a synoptical comparison of these practical examples is presented paying special attention on the use of ICT to support concrete recognition approaches. Further ideas to integrate ICT within these approaches are also introduced. To theoretically conceptualise and analyse the processes in the context of recognition of informal acquired competences beyond a mere descriptive level an institutional research perspective is required. So to examine the recognition of informal learning not only pedagogical theories but especially institutional theoretical approaches are relevant. Besides the competence theory and the certification theory the theoretical basis of the analysis is formed by the institution theory (particularly New Institutional Economics) and the governance approach (cf. Richter/Furubotn 2003 and Altrichter/Brüsemeister/Wissinger 2007)." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.2 Europa; Informelles Lernen; Anerkennung; Verfahren; Europa